Molecular Characterization of Tobacco Streak Virus, Beet Ringspot Virus, and Beet Ringspot Virus Satellite RNA from a New Natural Host, Phlox paniculata - Elena Motsar; Anna Sheveleva; Fedor Sharko; Kristina Petrova; Natalia Slobodova; Ramil Murataev; Irina Mitrofanova; Sergei Chirkov (Plants)
Phlox are ornamentals of great decorative value, grown throughout the world for their attractive flowers. Phlox cultivar collections at the Tsitsin Main Botanical Garden and the Botanical Garden of Lomonosov Moscow State University (both Moscow, Russia) were surveyed for virus diseases. Tobacco streak ilarvirus (TSV), beet ringspot nepovirus (BRSV), and BRSV satellite RNA (satRNA) were first detected in phlox when viromes of symptomatic Phlox paniculata plants were studied using high-throughput sequencing. The nearly complete genomes of three TSV and BRSV isolates and two BRSV satRNAs were assembled and characterized. TSV isolates shared 96.9–99.7% nucleotide sequence identity and were 82.2–89.1% identical to their closest relatives from broad bean, dahlia, and echinacea. BRSV isolates were distantly related to each other (83.7–89.3% identity) and were closest to those from oxalis and potato. BRSV satRNAs shared 90.6% identity and were 87.8–94.1% identical to satRNAs associated with tomato black ring virus L and S serotypes. Thus, TSV, BRSV, and BRSV satRNA were for the first time detected in a new natural host P. paniculata in Russia, adding to the list of known phlox viruses and expanding information on the host range, geographic distribution, and genetic diversity of these viruses.